Valle Inclan: The Grotesque Farce of Mr Punch the Cuckold - Valle-Inclán, Ramón del, 1866-1936 (Hispanic classics., 1991)
It may well be the sheer virtuosity of its writing that has deprived English audiences hitherto of an opportunity to appreciate Los cuernos de Don Friolera . This comic masterpiece by Spain's most innovative modern dramatist provides a provocatively sardonic treatment of marital infidelity and honourable revenge. Intricate in construction and thoughtful in the issues it raises, the play is nonetheless vivid in its impact as it veers disconcertingly between witty debate, uproarious farce and ludicrously overblown melodrama. The traditions and institutions which, in the 1920s (and, in some cases, for most of this century), blocked Spain's path to modernization and progress are mercilessly lampooned. The translation seeks to convey the dramatic point of the dialogue, its innuendos, allusions and shifts of register, rather than a strict literalness.